Sociodemographic profile and treatment seeking behaviour of animal bite patients attending the anti-rabies clinic at Patiala, Punjab - Singh, Aman Dev; Rochwani, Ritu (International Journal Of Community Medicine And Public Health, 2020)
Background: Rabies is an acute fatal viral disease. It can be prevented by eliminating exposures to rabid animals or by providing exposed persons prompt post exposure prophylaxis consist of local treatment of wounds in combination with appropriate administration of rabies immunoglobulin and vaccine. Aims and objectives were to study the sociodemographic profile of patients attending anti-rabies vaccination clinic and to study the treatment seeking behaviour and wound cleaning practices among them. Methods: This was a cross sectional study conducted among 150 randomly selected animal bite patients attended Anti Rabies Clinic, Department of Community Medicine G.M.C. Patiala from 1 November 2018 to 31 February 2019. Data collected and statistical analysis was done using epi info7. Results: Most of the patients were male 101 (67.34%). Out of 150 animal bite cases, majority of them were bitten by street dogs 135 (90%). It was found that 122 (81.34%) were category III bite, 26 (17.34 %) were category II bites and 2 (1.34%) were category I bite. Only 92 (61.34%) patients washed wound with water and soap. About 21 (14%) patients applied chilies or turmeric or oil on their wound. Conclusions: Majority of cases had bitten by dogs. Patients were less aware regarding proper wound care and seeking early treatment.